Rancang Bangun Sistem Pendeteksi ARTag sebagai Landasan Pacu AR.Drone Menggunakan Platform ROS (Robot Operating System) - Bakhtiar Alldino Ardi Sumbodo; Ariestyo Rahardian (IndoCEISS in colaboration with Universitas Gadjah Mada, Indonesia., 2018)
The development of quadrotor type AR. Drone for research are being developed. One of which is an object detection system based image processing to perform the mission, such as tracking, landing, or detect and pass the object hitch. Accordingly, in this research designed an ARTag detection system based on digital image processing using OpenCV library implemented in ROS platform used to connect the drone to PC which will then be carried out missions to landing. The method used is Thresholding, Contour Detection, and Image Moments.The result of this research is a system that able to detect ARTag objects along with his ID. The system is tested by computing time of the program in the static and dynamic state, detection performance testing in static and dynamic state, detection performance testing of the angle between the ARDrone and ARTag, detection performance testing of the light intensity, and testing landing mission. The conclusions are the optimal height of detection in the static and dynamic state is 150 cm, has excellent reliability to the light intensity, and the ARDrone can perform landing mission with a success rate of 70%.